Reasons for and consequences of resignations in Iraqi ministries, from the coronation of King Faisal until the signing of the 1922 treaty (Journal of the College of Basic Education, 2026)
The topic of the first ministerial resignations in the Iraqi Monarchical rule is a subject worthy of attention, given the numerous reasons accompanying those resignations. This is particularly significant because the heads of those ministries acted solely on orders from the British High Commissioner; however, at times they were unable to execute the High Commissioner's wishes as they represented a blatant violation of Iraqi sovereignty. The research addresses only two cabinets from the date of King Faisal's coronation until the signing of the 1922 Treaty, namely the second and third Al-Naqib cabinets. The research is divided into two sections: the first section deals with the second Al-Naqib cabinet and the circumstances surrounding its resignation, while the second section deals with the circumstances of the formation of the second Al-Naqib cabinet[*], followed by the resignation of some ministers and the subsequent resignation of the entire cabinet.